Holiday in the islands of grief - McDaniel, Jeffrey, 1967- (Pitt poetry series., 2020)
"In his new collection, Jeffrey McDaniel confronts the insular and expansive qualities of loss. With electric language and surrealistic imagery, McDaniel's poems deliver the quotidian elements of middle-age life while weaving us in & out of childhood and adulthood alongside body and mind. The tragic and life affirming share the same page and the same world, reminding us how close corruption can be to innocence; domesticity to fantasy; aging to youth. Jonathan We are underwater off the coast of Belize. The water is lit up even though its dark as if there are illuminated seashells scattered on the ocean floor. We're not wearing oxygen tanks, yet staying underwater for long stretches. We are looking for the body of the boy we lost. Each year he grows a little older. Last December I opened his knapsack and stuck in a plastic box of carrots. Even though we're underwater, we hear a song playing over a policeman's radio. He comes to the shoreline to park and eat midnight sandwiches, his headlights fanning out across the harbor. And I hold you close, apple of my closed eye, red dance of my opened fist."--EBSCO